How Self Efficacy in Mathematic Based on Gender Perspective? - Kasturi Kasturi; Sulton Sulton; Agus Wedi (Edcomtech, 2021)
This study aims to determine whether there are differences in self efficacy between middle school male and female students in Mathematics. This research is a quantitative study to find out the level of self efficacy in 108 male students and 118 female students of class VIII middle school, using a self efficacy questionnaire consisting of reasoned statement items with a reliability value of 0.844. The analysis showed that the average self efficacy in mathematics learning for male students was 92.77 and for women 90.27 of the maximum value of 120, was in the high category. This shows that most male and female students have great confidence in solving mathematical problems. Therefore, it can be said that there is no significant difference in mathematical self efficacy between male and female students